The Role of Mca/Ua Pulsatility Index Ratio in Managing Preeclampsia and Gestational Hypertension: A Prospective Study - Dr. T. Shireesha, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Preeclampsia and gestational hypertension pose significant risks to both mother and fetus. The middle cerebral artery to umbilical artery (MCA/UA) pulsatility index ratio may serve as a valuable tool in predicting and managing adverse outcomes. Methods: In a prospective observational study, 200 pregnant women with preeclampsia or gestational hypertension were assessed using Doppler ultrasound to determine the MCA/UA PI ratio. Participants were grouped into cases (ratio ≤1) and controls (ratio >1). Maternal and neonatal outcomes were analyzed. Results: The study found that 52 women (26%) had an MCA/UA PI ratio ≤1. These cases had a higher progression to severe preeclampsia and eclampsia (p<0.00001), increased incidence of severe oligohydramnios (p<0.0001), and higher rates of emergency cesarean sections (p=0.00027). Neonatal complications, including low birth weight, low Apgar scores, and NICU admissions, were significantly higher in cases. Conclusion: The MCA/UA PI ratio is a significant predictor of both maternal and neonatal adverse outcomes in preeclampsia and gestational hypertension. Utilizing this ratio can enhance clinical decision-making and improve management strategies.